A new species of Gieysztoria Ruebush & Hayes, 1939 (Platyhelminthes, Rhabdocoela, Dalyelliidae) from Argentina with comments on geographical distribution of the genus in the Neotropical region - Adami, Mariana Laura (2024)
A new Gieysztoria species from limnic environments in Argentina is described. The Neotropical biogeographic distribution of the genus is provided and its relation to stylet morphology is discussed. Gieysztoria reta n. sp. differs from its congeners in terms of stylet shape and length. The complex stylet is 50 -75 μm long, with a fenestrate fibrous girdle. Distally it has four sets of spines: the largest, robust, ventral fang-shaped spine slightly curved toward the center and proximately grooved; a shorter ventral fang-shaped spine; a dorsal group of seven to eight fine spines arranged like bristles; and a group of 12 to 13 dorsal hollow, broad-based spines of different lengths. These are arranged in three rows, forming a fan shape. The arrangement of its genital muscle system is described using rhodamine-labeled phalloidin and confocal laser scanning microscopy (CLSM), a novel methodological approach for this genus. The major finding by using this method is that we have been able visualize the 3D of genital system structure and relationship among different sets of muscles fibers both in the female and male genital organs.